Pengaruh Sumber Daya Manusia dan Ekonomi Kreatif pada Peningkatan Parawisata Halal Pantai Lon Malang di kabupaten Sampang - Syah Pahlevi, Muhammad Resa; Muhammad Wildan Alkirom (Institut Agama Islam Negeri Madura, 2024)
Madura Island has many halal tourism destinations that need to be developed, one of which is Lon Malang beach which is located in Sampang Regency, the Regency is known for its people who are very thick with Islamic teachings. This study aims to determine the factors that influence the increase in Halal Tourism in terms of human resources and creative economy. The population and sample in this study were 91 respondents consisting of 37 administrative staff and 54 field workers who are creative economic actors in the halal tourism area of Lon Malang Beach, Sampang Regency, using a quantitative descriptive approach. The data analysis method uses measurement model analysis (Outer Model) and structural model analysis (Inner Model), while hypothesis testing uses t statistical test (partial) and f statistical test (simultaneous) which is assisted by statistical aids, namely SmartPLS version 3.0 software. The results showed that: 1) Human Resources has a significant effect on increasing halal tourism, 2) Creative Economy has a significant effect on Increasing Halal Tourism, 3) Human Resources and Creative Economy have a significant effect simultaneously on Increasing Halal Tourism.